The importance of using body language in teaching the lower grades from the point of view of public school teachers in Jenin - An exploratory study - Abdelghafoor, Nedal Fayez (Journal of Educational and Psychological Sciences, 2020)
The study aimed to highlight the importance of using body language in the teaching process and determining the importance of using it in teaching the lower grades from the point of view of public school teachers in Jenin The study was followed the descriptive/exploratory method, where the researcher conducted an extensive survey of related literature to achieve the first objective, while the field data were collected by a questionnaire consisting of (34) items divided into three areas: teacher, learner, Classroom management, it was implemented on a sample of (125) teachers. The findings indicated that the use of body language acquire a great importance in more than one aspect of the educational process(learner, Teacher, Class management), and showed that the level of teachers awareness of the importance of using body language in teaching process came in a high degree. Regarding to the variables, the findings showed that there were statistically significant differences due to the sex variable in teachers’ awareness degree at the level of the learner domain and classroom management domain, in favor of females, while the findings showed that there were no differences at the level of teacher domain and the tool due to the sex variable, and no differences due to the years of experience variable at the level of the tool and its three fields In the light of mentioned results, a set of recommendations were addressed to teachers and the educational institution officials and researchers.